A cyanide-sensing detector in aqueous solution based on anion–π interaction-driven electron transfer. Issue 7 (4th March 2019) - Men, Guangwen; Han, Wenkun; Chen, Chunrong; Liang, Chunshuang; Jiang, Shimei
Abstract : A "turn on" fluorescent and colorimetric chemosensor for cyanide was developed based on anion–π interaction-induced electron transfer. Abstract : A "turn on" fluorescent and colorimetric sensor, HAT(CN)6, was developed for the light-up detection of cyanide. It was implemented through its strong anion–π interaction, inducing thermal CN − → HAT(CN)6 electron transfer, to give the dianion product [HAT(CN)6 ] 2−, which exhibits unexpected fluorescence. The sensor shows high selectivity, rapid response and a low detection limit towards CN − in aqueous solution, hence indicating its enormous potential in practical applications.